CHARACTERISTICS OF REFRACTIVE ERRORS IN CHILDREN WITH ALLERGIC CONJUNCTIVITIS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of refractive errors in children with allergic conjunctivitis presenting to Hanoi Medical University Hospital from January to December 2025.Subjects and Methods: A cross-sectional descriptive study was conducted on 33 patients aged ≤ 18 years diagnosed with allergic conjunctivitis. Data collected included duration of symptoms and refractive error indices such as best-corrected visual acuity and classifications of myopia, astigmatism, and hyperopia.Results: Among the eyes evaluated, 33.4% were non-myopic, 12.1% had low myopia, and 4.5% had high myopia. Astigmatism was the most prevalent refractive error, with low astigmatism observed in 25.8% of right eyes and 57.6% of left eyes. Moderate astigmatism accounted for 16.7% in right eyes and 28.8% in left eyes, while high astigmatism was present in 3.0% of right eyes and 4.5% of left eyes. Regarding hyperopia, low hyperopia predominated in both eyes, and moderate and high hyperopia were less frequent at 3.9% and 2.0% per eye, respectively.Conclusion: Children with allergic conjunctivitis demonstrate varied refractive error profiles, with astigmatism being the most common. Refractive assessment should be routinely incorporated into clinical evaluation to support comprehensive screening, management, and visual protection.
Keywords: Allergic conjunctivitis, refractive errors, astigmatism, myopia, hyperopia.